Enhanced method for evaluating remodeling floor plans for apartment complexes with an emphasis on efficiency and accuracy - Moon, Jae Sang; Park, Junseok; Kim, Jinyoung (Journal of Building Engineering, 2024)
A social issue in Korea has recently emerged regarding the structural performance and living environment improvement of aged apartment houses (i.e., 20 or more years old). The available methods to improve the issues related to aged apartment houses are remodeling and reconstruction, and there is a trend to recommend environmentally friendly remodeling. During the initial design stage of a typical remodeling project, several floor plan drafts are prepared and undergo several revisions to produce the final floor plan. As such, this study aims to develop a program capable of promptly offering quantitative structural guides during the initial design stage, thereby reducing the duration and workforce required to complete the final floor plan. The developed program was utilized to conduct a structural evaluation of five existing apartment complexes in Korea. Subsequently, to validate the usability of the developed program, the accuracy and time efficiency of its evaluation results were compared to those using commercial structural analysis software. While the calculated structural indices showed a variance within 5 % between the two programs, there were considerable differences in processing time, at 35 min vs. 8–16 h per building. Therefore, the program developed in this study will be beneficial during the initial design stage, and it will significantly reduce the time, effort, and cost necessary for decision-making in a remodeling project while maintaining accuracy in structural assessment.
Keywords: Aged apartments; Apartment complexes; Automated evaluation; Design stage; Floorplans; Initial design; Living environment; Remodeling; Social issues; Structural performance; Aged apartment; Automated evaluation; Floor plan; Remodeling; Structural performance